Analisis Nilai Sudut Deviasi pada Prisma menggunakan Software Crocodile Physics 605 - Rahel Rehuella Marpaung; Nabeela Rahma Noor Aziz; Popi Purwanti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
Understanding a physics concept requires supporting activities such as practicum. The existence of the Covid-19 Pandemic has caused practicum not to be carried out directly in the laboratory so it is done through virtual laboratory media, one of which is the Crocodile Physics software. However, the use of Crocodile Physics software for prism practicum has not been widely used. Therefore, in this study using Crocodile Physics 605 software which aims to determine the angle of deviation in different prisms and to see the relationship between the angle of incidence and the angle of deviation of the prism. Based on the data analysis that has been carried out, it is found that the benzane medium produces the largest prism deviation angle compared to other mediums, which is 62o. The greater the value of the angle of incidence in the first plane of the prism , the greater the value of the angle of deviation . Vice versa, the smaller the value of the angle of incidence in the first plane of the prism, the smaller the value of the angle of deviation.